Metaphors for social media‐enhanced foreign language teaching and learning - Reinhardt, Jonathon (Foreign language annals, 2020)
As L2 (foreign and second language) instructors and materials designers are faced with online and distance learning mandates, new perspectives on how to use familiar, everyday technologies that learners can access from home like social media are welcome. Imagining these new uses, however, may require going beyond the traditional computer‐assisted language learning (CALL) metaphors of computer‐as‐tutor or tool, which were established before social media. This article outlines four new metaphors that better capture the new user dynamics of social media: windows, mirrors, doorways, and playgrounds. After a discussion of the brief history of CALL metaphors, these new metaphors are presented with support from research alongside ideas for L2 teaching and learning. The Challenge Social media—Facebook, Twitter, YouTube, and so forth—are ubiquitous and popular among learners, but how can they be used for formal L2 learning purposes? How can we conceptualize the design of social media‐enhanced learning activities? This article presents four metaphors for thinking about the value of social media for L2 learning: windows, mirrors, doorways, and playgrounds.